Experience of the new seizure diary in the Free State and Northern Cape - Chika K. Egenasi; Anandan A. Moodley; Wilhelm J. Steinberg; Gina Joubert (South African Family Practice)
Background: Epilepsy is a neurological disease affecting adults and children globally. A seizure diary is one of the self-management tools for tracking seizures. This study aims to ascertain the experience of a new seizure diary by persons completing the diary in the Free State and Northern Cape of South Africa.